Calibration of naturally fractured reservoir models using integrated well-test analysis – an illustration with field data from the Barents Sea. Issue 1 (2022) - Egya, David O.; Corbett, Patrick W. M.; Geiger, Sebastian; Hegndal-Andersen, Jens-Petter Norgard and Søren
No abstract available